How much biochar is safe? Exploring potential ecotoxicological consequences for soil invertebrates and plants - Costa, Vanessa Borges da [UNESP]; Ogura, Allan Pretti; Alexandre, David Silva; Soares, Matheus Bortolanza; Alleoni, Luís Reynaldo Ferracciú; Espíndola, Evaldo Luiz Gaeta; Pinto, Thandy Junio da Silva (Elsevier, 2024)
The application of biochar in soil has shown promising potential for mitigating the toxicity of contaminated soils due to its unique properties. However, the understanding of its adverse effects on soil biota remains limited. This study aimed to investigate the potential ecotoxicological effects of incorporating sugarcane straw biochar into clay and sandy soils. This research assessed three biochar dosages (2 %, 5 %, and 10 %) and their effects on four species: the springtails Sinella curviseta and Proisotoma minuta, the worm Enchytraeus crypticus, and the plant Eruca sativa L. The results revealed that biochar incorporation had positive effects on plant growth, increasing biomass, and shoot and root length in E. sativa, with more pronounced effects in clay soil. However, the effects on the survival, reproduction, and growth of springtails varied depending on the species and soil type, with a reduction in the survival of P. minuta in both soils (2,2 and 2,9 times lower in clay soil and sandy soil respectively) and S. curviseta only in clay soil (24 % to 36 % decrease). The reproduction of P. minuta decreased in both soils (34 % - 48 % in sandy soil and 50 % - 80 % in clay soil), while the reproduction of S. curviseta decreased only at the lowest proportion of biochar in the clay soil (18 % decrease). For E. crypticus, biochar improved both survival and reproduction, especially in sandy soil (1.9 and 11 times greater respectively). Therefore, biochar has positive effects on worms and plants, indicating the potential to improve soil health and support ecosystem resilience, but it has deleterious effects on springtails at certain dosages. The effects of biochar amendments on soil characteristics and the effects of biochar-induced toxicity should be considered to avoid potential risks to representative species. The findings presented herein address lacunae in ecotoxicology by delineating safe concentrations of biochar for various soil species, thus paving the way for subsequent validation of optimal application doses.
Keywords: Growth; Organisms; Pyrolysis; Reproduction; Survival; Toxicity